2020
DOI: 10.1016/j.scitotenv.2019.134807
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and distribution of microplastics in the coastal mangrove sediments of China

Abstract: h i g h l i g h t s First comprehensive study on MPs in mangrove sediments along the coast of China. The MPs abundance in mangrove sediments was up to 8.5 times higher than in mangrove free sediments. The sandy sediments were dominated by foams, and the muddy sediments by fibers and fragments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 41 publications
2
47
1
2
Order By: Relevance
“…Nor and Obbard [25] reported averages of 12 to 63 MPs/kg in mangroves of Singapore while Zhang et al [59] reported MP averages ranging from 273 to 3520 MPs/kg in mangroves further away from the city and mangroves closer to industrial/urban zones, respectively, in China. Based on these and other recent reports (e.g., [28,30,60]), South African mangroves can, therefore, be considered moderately (e.g., St. Lucia) to highly (e.g., Isipingo) polluted by MPs compared with other parts of the world. This is concerning when one considers that South Africa is a developing country with high population growth [61], limited consumer and environmental awareness, and multiple waste management inadequacies [62].…”
Section: Abundance Of Microplastics In Mangrove Sedimentmentioning
confidence: 70%
See 1 more Smart Citation
“…Nor and Obbard [25] reported averages of 12 to 63 MPs/kg in mangroves of Singapore while Zhang et al [59] reported MP averages ranging from 273 to 3520 MPs/kg in mangroves further away from the city and mangroves closer to industrial/urban zones, respectively, in China. Based on these and other recent reports (e.g., [28,30,60]), South African mangroves can, therefore, be considered moderately (e.g., St. Lucia) to highly (e.g., Isipingo) polluted by MPs compared with other parts of the world. This is concerning when one considers that South Africa is a developing country with high population growth [61], limited consumer and environmental awareness, and multiple waste management inadequacies [62].…”
Section: Abundance Of Microplastics In Mangrove Sedimentmentioning
confidence: 70%
“…For example, the system that was the least anthropogenically disturbed exhibited the highest concentration of fibres ( Figure 6) and the highest proportion of fine (<125 µm) sediment, while the most disturbed system exhibited lower concentrations of fibres and the lowest proportion of fine sediment. This suggests that mangroves characterised by very fine sand/mud may harbour more fibres than other particle types [60]. However, it should be noted that several studies [25,32,64,68] have reported no clear relationship between MP abundance and sediment size, highlighting the need to understand how edaphic factors influence MP deposition and how deposited MPs may, in turn, influence the soil characteristics.…”
Section: Relationship Between Microplastics In Mangrove Sediment and mentioning
confidence: 99%
“…The distribution of thin-lm microplastics could result from the transport of nearby salt elds or the fragmentation of plastic mulch used in horticulture (de Jesus Piñon-Colin et al 2018). More than 93% of microplastics in the beach sands and sea sediments of mangroves are fragmented, predicting the origin of microplastics as secondary sources from large plastic fragments (Zhou et al 2020). These conclusions are relatively appropriate with the proportion of microplastic shapes due to different anthropogenic activities of the sampling sites.…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…K. obovata adapts to transitional ecosystems where the land and ocean meet by overcoming periodic and aperiodic tidal effects, which induce high salinity, severe erosion, and anaerobic conditions 8 . K. obovata plays a crucial role in protecting biodiversity and combating erosion 9,10 . Specifically, the mangrove K. obovata can protect the embankment, accelerate the natural deposition of the beach, filter organic matter and pollutants from inland areas, and provide an ideal habitat for the marine flora and fauna 11 .…”
Section: Introductionmentioning
confidence: 99%